A Review Paper on Concrete-Filled Aluminum Tubular Columns (Journal of University of Babylon for Engineering Sciences, 2019)
The aim of this review paper is to summarize available reports, papers, theses, dissertations and conference papers dealing with the performance of aluminum-concrete composite columns. Hollow aluminum sections filled with concrete have been used as composite columns due to their corrosion resistance, easy production, appearance and lightweight. Many researches were performed in the area of concrete-filled hollow sections (tubes). However, there are few researches have been performed on concrete-filled aluminum tubes. In this review, different available published papers are summarized to view the type of the studied aluminum-concrete columns and the main studied parameters that affecting the behavior of these composite columns. More than (190) specimens are collected and showed in this review.